2010
DOI: 10.1161/strokeaha.110.586842
|View full text |Cite
|
Sign up to set email alerts
|

Stratified, Urgent Care for Transient Ischemic Attack Results in Low Stroke Rates

Abstract: Background and Purpose-Transient ischemic attack (TIA) is a marker for early risk of stroke. No previous studies have assessed the use of urgent stroke prevention clinics for emergency department (ED) patients with TIA. We hypothesized that an ABCD2-based ED triaging tool for TIA with outpatient management would be associated with lower 90-day stroke rate than that predicted by ABCD2. Methods-A cohort of prospectively identified patients presenting with symptoms suggestive of TIA seen in 2 tertiary-careEDs. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
4
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 17 publications
3
89
4
5
Order By: Relevance
“…Eleven were population-based studies including cohorts from the UK (Oxford), Ireland (Dublin), USA (Texas and Minnesota), Canada (Alberta) and northern Portugal. 9 23,127,129,131,135,136,143,149,153,159 and by both in four; 62,158,162,163 in three studies 120,138,155 this information was not reported.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 95%
See 3 more Smart Citations
“…Eleven were population-based studies including cohorts from the UK (Oxford), Ireland (Dublin), USA (Texas and Minnesota), Canada (Alberta) and northern Portugal. 9 23,127,129,131,135,136,143,149,153,159 and by both in four; 62,158,162,163 in three studies 120,138,155 this information was not reported.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 95%
“…telephone interviews, medical records, letters) in 11 studies, 65,131,[146][147][148]153,154,158,160,162,163 and was not reported in two studies.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…9,10 The rapid initiation of antiplatelet agents and early assessment in a dedicated stroke prevention clinic can cut this risk dramatically, and both interventions were used in our cohort, 14,21,22 as evidenced by a relatively low overall rate of stroke. Despite these interventions, patients with isolated aphasia in this study had double the rate of stroke at all time points assessed and a 7.3% rate of stroke at 90 days.…”
Section: Discussionmentioning
confidence: 99%